2004
DOI: 10.1146/annurev.cellbio.20.010403.105057
|View full text |Cite
|
Sign up to set email alerts
|

New Developments in Mitochondrial Assembly

Abstract: The mitochondrion has developed an elaborate translocation system for the import of nuclear-coded proteins and the export of proteins coded on the mitochondrial genome. Precursor proteins contain targeting and sorting information to reach the mitochondrion, whereas the translocons recognize the information and direct the precursor to the correct compartment. The outer membrane contains the TOM (translocase of the outer membrane) complex for translocation and the SAM (sorting and assembly machinery) complex for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
262
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 273 publications
(262 citation statements)
references
References 151 publications
0
262
0
Order By: Relevance
“…Dissociation of the membrane potential (⌬ ) before import by the addition of the K ϩ -ionophore valinomycin in the presence of K ϩ in the buffer did not affect transport of the precursor to a protease-protected location ( Figure 1B, lane 6). Because protein transport across the inner mitochondrial membrane depends on ⌬ (Neupert, 1997;Jensen and Dunn, 2002;Koehler, 2004;Rehling et al, 2004), we concluded that Taz1 was not transported across the inner membrane.…”
Section: Import Of Taz1 Into S Cerevisiae Mitochondriamentioning
confidence: 89%
“…Dissociation of the membrane potential (⌬ ) before import by the addition of the K ϩ -ionophore valinomycin in the presence of K ϩ in the buffer did not affect transport of the precursor to a protease-protected location ( Figure 1B, lane 6). Because protein transport across the inner mitochondrial membrane depends on ⌬ (Neupert, 1997;Jensen and Dunn, 2002;Koehler, 2004;Rehling et al, 2004), we concluded that Taz1 was not transported across the inner membrane.…”
Section: Import Of Taz1 Into S Cerevisiae Mitochondriamentioning
confidence: 89%
“…Recent work by Youle, Jensen, Koehler, Scorrano and others has revealed a role for mitochondrial shape in apoptosis. [74][75][76][77][78] In particular, mitochondria typically fragment during apoptosis and inhibition of fission blocks cell death. Are the fission and fusion proteins Drp1, Opa1 or endophilin B candidates for Bax partners?…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Tom20 is thought to be responsible for the import of preproteins bearing classical matrix-directed N-terminal signal sequences, or leader peptides. Tom70, the alternate receptor, is thought to mediate the import of preproteins that contain targeting information within their mature sequences (Koehler, 2004;Rehling et al, 2004). Although much of our knowledge of import derives from work in Saccharomyces cerevisiae and Neurospora crassa, the biological functions of the human Tom70 and Tom20 receptors seem to be largely conserved (Iwahashi et al, 1997;Schleiff et al, 1997;Yano et al, 1997;Suzuki et al, 2002).…”
Section: Introductionmentioning
confidence: 99%